Improved single visit management of old infected iatrogenic root perforations using Biodentine® - Davide Mancino; Florent Meyer; Youssef Haikel (Ariesdue, 2018)
Aim: The aim of this retrospective observational case series study was to evaluate the middle term outcomes on endodontic management of old infected iatrogenic root perforations using Biodentine. The treatments were always concluded in a single visit, without previous medication with calcium hydroxide. Our goal was to facilitate this kind of treatments and to make them more reproducible and manageable even for a general practitioner or a student. Methodology and methods: Between January 2011 and June 2016, 51 patients with old infected root perforations have been enrolled. All the treatments were performed using Biodentine in a single visit. Infected root perforation repair was performed by supervised dental students (39%) or a qualified endodontist (61%), employing surgical microscope magnification during treatments. After the treatment, the 51 patients were monitored for 18-64 months. We used clinical and radiographic examinations. Results: Of 51 examined teeth, 48 (94%) were classified as healed. The time, the size and the location of the perforations did not have a significant effect on the outcome. We proved the ineffectiveness of the null hypothesis. According to this latter, the single visit treatment of old infected perforations with Biodentine was inadequate. Conclusions: In single visit treatments, Biodentine seems to provide a biocompatible and effective seal in acidic environment, in accidental root perforations, even if the treatment is performed by an inexperienced operator and regardless of the location, the size and the time of occurrence of the perforation. Riassunto: Obiettivi: Lo scopo di questo studio osservazionale retrospettivo è stato quello di valutare la percentuale di guarigione a medio termine nel trattamento delle "old infected" perforazioni con contaminazione batterica usando biodentine. Il trattamento di tutte le perforazioni è stato fatto in seduta singola, senza medicazione con idrossido di calcio. Altro obiettivo è stato quello di facilitare questo tipo di trattamenti, rendendoli riproducibili e fattibili anche per un dentista generico o uno studente. Materiali e metodi: Tra Gennaio 2011 e Giugno 2016, abbiamo selezionato 51 pazienti con "old infected" perforationi. Ogni caso é stato trattato con Biodentine in singola seduta. Il 39% dei casi é stato trattato da studenti della clinica universitaria sotto la supervisione di un tutor senior, mentre il 61% da un endodontista qualificato, usando il microscopio operatorio durante ogni fase del trattamento. Dopo il trattamento, i 51 pazienti sono stati monitorati tra 18 e 64 mesi, con esami radiografici e clinici. Risultati: Fra i 51 denti esaminati, 48 (94%) sono stati classificati come guariti. Nel nostro studio il tempo, la dimensione e la localizzazione della perforazione non hanno avuto alcun valore prognostico. Abbiamo dunque rigettato l'ipotesi nulla, secondo la quale il trattamento in singola visita delle "old infected" perforazioni con Biodentine fosse inadequato. Conclusioni: Il trattamento delle "old infected" perforazioni in ambiente acido in singola visita con Biodentine sembra assicurare un sigillo biocompatibile e tridimensionale della perforazione anche se il trattamento è stato eseguito da operatori senza tanta esperienza (studenti), indipendentemente dalla localizzazione, dimensione e tempo dell'avvenuta perforazione. Keywords: Iatrogenic perforation, Acidic environnement, Bioactivity, Biodentine, Single visit, Parole chiave: Perforazione iatrogena, Ambiente acido, Bioattività, Biodentine, Singola visita